Pharmacokinetic Interpretation of Cephradine Levels in Serum After Intravenous and Extravascular Administration in Humans - Rattie, Elisabeth S. (1976)
Pharmacokinetic parameters were calculated from intravenous data based upon a two-compartment open model. These parameters were subsequently used to determine the absorption rates and bioavailability of cephradine administered intramuscularly and orally. The results indicate that cephradine obeys dose-independent kinetics and that biological availability is complete from all dosage forms.